Eksplorasi Nilai-nilai Islam dalam Upaya Mencetak Generasi Unggul pada Siswa Madrasah Ibtidaiyah - Farhan Rifqi Attijani; Muhammad Abdul Halim Sidiq; Ziaulhaq Fathullah (Edu Happiness: Jurnal Ilmiah Perkembangan Anak Usia Dini, 2025)
This study aims to explore Islamic religious values in an effort to create a generation of superior students at MI Nurul Islam Yosowilangun Kidul Lumajang. The research method used is qualitative, with data collection through interviews, observations, and documentation studies. The results showed that the application of Islamic religious values in the Mabadiul Fiqiyah book program was able to improve students' understanding of Islamic teachings and help produce a generation of students with noble character and faith. The learning carried out is effective in improving students' ability to understand and apply Islamic religious values in everyday life, so the program implemented by MI Nurul Islam is very suitable for preparing students towards the formation of superior santri character.